ALTERNATIVE INVESTMENT FUNDS: REGULATION, CHARACTERISTICS AND DEVELOPMENT IN LITHUANIA - Jarašius, Gytis (Ekonomika, 2012)
This article deals with the operations of alternative investment funds (AIF) and their legislation in Lithuania. Currently, the AIF registered in Lithuania face difficulties, since the majority of them are not able to attract investors and are forced to discontinue their operations. Nevertheless, the size of the AIF capital in Lithuania is consistently growing and contributes to the increasing share of capital among all investment funds. The legislation of AIF on the global scale before the financial and economic crisis in 2008 was rather weak; nevertheless,currently this trend is changing, a new legislation is put in place in the EU and USA in order to tighten AIF legislation and to limit their operations. However, AIF registered in Lithuania are rather small; therefore, this trend will not have a significant influence on Lithuania.